Game theory and international environmental co-operation: A survey with an application to the Kyoto-Protocol - Michael Finus (Fondazione Eni Enrico Mattei (FEEM), 2000)
First, the paper lays out the fun-damental assumptions underlying the game theoretical analysis of international environmental problems. Second it summarises important findings which help to explain the difficulties of co-operation and discusses remedies. Chapter 3 looks at measures to avoid asymmetric welfare distributions and to enforce an IEA. Chapter 4 discusses policy instruments in global pollution control and chapter 5 summarises the results on the formation of coalitions. Third, the results of chapters 3, 4 and 5 are critically re-viewed. On the one hand, open issues with respect to the theoretical analysis are characterised. On the other hand, practical problems which are not covered by theory are mentioned and evaluated as to their effect to influence policy conclusions. Fourth, the theoretical results and the derived conclusions of chapters 3 to 5 are applied to the analysis of the Kyoto-Protocol (chapter 6). The article stresses the intuition behind all results, though formal proofs of some new results are given.
Keywords: C72; D62; D74; Q20; Q28; 330; Game theory; international environmental agreements; Kyoto-Protocol; Internationale Umweltpolitik; Spieltheorie; Kooperatives Spiel; Umweltabkommen; Klimaschutz; Verhandlungstheorie; Theorie